2012
DOI: 10.1134/s1061933x12030118
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation and complexation in a series of tetramethylenesulfonate-substituted calix[4]resorcinarenes

Abstract: NMR methods are employed to study the effects of inorganic salts, solvents, and guest molecules of methylviologen (MV 2+ ) and choline (Ch + ) on the aggregation properties of water soluble tetramethylene sulfonate substituted calix[4]resorcinarenes containing methyl (1), amyl (2), and heptyl (3) substituents in the lower rim. It is established that, in aqueous solutions at concentrations of 1-10 mM, compound 1 exists in the monomeric form; the size of aggregates of amphiphilic compound 2 gradually increases (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…[26][27][28] Studies reveal a range of aggregate sizes (N agg ) for tetramethylene sulfonatesubstituted calix [4]resorcinarenes, demonstrating the influence of functionalization on self-assembly. 29 Functionalization plays a key role, with hydrogen bonding and metal coordination being the most common drivers. Vesicles, micelles, and nanoparticles are observed in water, while AFM studies revealed unexpected layered structures in amphiphilic calixarenes.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28] Studies reveal a range of aggregate sizes (N agg ) for tetramethylene sulfonatesubstituted calix [4]resorcinarenes, demonstrating the influence of functionalization on self-assembly. 29 Functionalization plays a key role, with hydrogen bonding and metal coordination being the most common drivers. Vesicles, micelles, and nanoparticles are observed in water, while AFM studies revealed unexpected layered structures in amphiphilic calixarenes.…”
Section: Introductionmentioning
confidence: 99%
“…This amphiphilic behavior of tetrasulfonate derivatives (SR) has created new avenues for harnessing resorcinarenes in biological applications. 30,31 The representative examples of SRs studied in the literature include, methylenesulfonate groups appended at the upper-rim C2positions (Type-1), [30][31][32][33][34][35][36][37][38][39][40][41] sulfonate and phenolic oxygens linked by methylene chains (Type-2), 42 and alkylated sulfonate derivatives at the lower-rim (Type-3). [43][44][45] The nature of their binding to neutral, singly and doubly charged aliphatic/N-heterocycle cationic guests has been studied in solution to understand the sulfonate groups intricate role in H-G systems.…”
Section: Introductionmentioning
confidence: 99%